2019
DOI: 10.1016/j.mvr.2019.103908
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and peripheral vascular function in healthy individuals with low cardiovascular risk

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…Indeed, it has been shown that, in hypertensive patients, NO www.nature.com/scientificreports/ availability is reduced early in the course of the disease 29 . Although we did not measure either the level of NO or antioxidative markers in our current cohort of patients, in the light of our previous discovery showing that retinal microvascular dysfunction occurs in parallel with changes observed in the level of oxidative stress both in normal 19 and individuals with abnormal BP levels 15 , it is logic to presume that similar abnormalities occurred in our current cohort of individuals with ESC/ESH grade 1 hypertension, thus contributing to the abnormal retinal microvascular function measured in these individuals. Our ESC/ESH grade 1 hypertension also exhibited abnormal retinal venous response to flicker.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Indeed, it has been shown that, in hypertensive patients, NO www.nature.com/scientificreports/ availability is reduced early in the course of the disease 29 . Although we did not measure either the level of NO or antioxidative markers in our current cohort of patients, in the light of our previous discovery showing that retinal microvascular dysfunction occurs in parallel with changes observed in the level of oxidative stress both in normal 19 and individuals with abnormal BP levels 15 , it is logic to presume that similar abnormalities occurred in our current cohort of individuals with ESC/ESH grade 1 hypertension, thus contributing to the abnormal retinal microvascular function measured in these individuals. Our ESC/ESH grade 1 hypertension also exhibited abnormal retinal venous response to flicker.…”
Section: Discussionmentioning
confidence: 88%
“…Beside its direct effect on the vascular functionality, hypertension is also known to cause an acceleration of the ageing process of the vascular function 29 . We have previously demonstrated that, in ageing, normal individuals there is a decline in retinal vasoregulative capacity in both dilatory and constrictory phases that was independent of any systemic influences 17 and we have linked this abnormal response to the possibility of an age-related increase in oxidative stress 19 . Nevertheless, the subjects included in the current paper were much younger that those included in our ageing studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An aTR below 1 was considered poor cardiovascular reactivity (high risk), whereas an aTR between 1 and 2 was considered intermediate vascular reactivity (medium risk). An aTR of >2 was considered a sign for normal peripheral vascular reactivity (Karimzad, Shokr & Gherghel 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, many methods were developed to evaluate functional microvascular responses to biological stimuli in different vascular beds [ 2 ]. One of these methods, the dynamic retinal vessel analysis (DVA), was highlighted as one of the most sensitive and reliable methods to measure early vascular changes that point out early endothelial dysfunction and future risk of cardiovascular pathologies in individuals with and without overt clinical symptoms [ 3 , 4 , 5 ]. Moreover, it has also been shown that retinal microvascular function is modified by age [ 6 ].…”
Section: Introductionmentioning
confidence: 99%